Drug desensitization in allergic children - Caimmi, Silvia; Caffarelli, Carlo; Saretta, Francesca; Liotti, Lucia; Crisafulli, Giuseppe; Cardinale, Fabio; Bottau, Paolo; Mori, Francesca; Franceschini, Fabrizio; Bernardini, Roberto; Marseglia, Gian Luigi (Acta Biomedica Atenei Parmensis, 2019)
Drug allergy is an increasing problem worldwide, affecting all populations and races, children and adults, and for which diagnosis and treatment are not well standardized yet. Besides classical treatments, new drugs have been developed, especially for patients suffering from malignancies and chronic inflammatory diseases, that specifically target the cause of the disease. For those patients requiring such molecules, it is sometimes difficult to find an alternative drug when hypersensitivity reactions occur. Desensitization is therefore the best option whenever no alternative therapy is available but also when alternative treatments are considered therapeutically inferior and or more toxic. Despite its clinical success, little is known about the mechanisms and molecular targets of drug desensitization. Desensitization protocols use a gradual dose escalation to allow the safe administration of a treatment to which a patient previously presented a hypersensitivity reaction. The procedure requires special training and coordination of an allergy team, including physicians, nurses, and pharmacists, working together to safely and successfully implement desensitization protocols when appropriate. There is no difference in desensitization protocol between adults and children, except for the final cumulative dose of the administered drug.